2015
DOI: 10.1007/s12020-015-0719-2
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of dihydrotestosterone and estradiol on apoptosis in the anterior pituitary gland from male rats

Abstract: Hormones locally synthesized in the anterior pituitary gland are involved in regulation of pituitary cell renewal. In the pituitary, testosterone (T) may exert its actions per se or by conversion to dihydrotestosterone (DHT) or 17β-estradiol (E2) by 5α-reductase and aromatase activity, which are expressed in this gland. Previous reports from our laboratory showed that estrogens modulate apoptosis of lactotropes and somatotropes from female rats. Now, we examined the in vitro and in vivo effects of gonadal ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Accumulating evidence suggests that estrogen plays multiple physiological roles in cellular biology, including apoptosis (Ying 2000, Jaita et al 2005, Zarate et al 2009, Magri et al 2016. Jaita et al demonstrated that E 2 induces apoptosis of anterior pituitary lactotropes by upregulating the Fas/FasL system (Jaita et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that estrogen plays multiple physiological roles in cellular biology, including apoptosis (Ying 2000, Jaita et al 2005, Zarate et al 2009, Magri et al 2016. Jaita et al demonstrated that E 2 induces apoptosis of anterior pituitary lactotropes by upregulating the Fas/FasL system (Jaita et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the male, 17β-estradiol exerts rapid apoptotic action in lactotropes, somatotropes, or gonadotropes cells of pituitary gland. However, the effects of gonadal steroids on the expression of Bcl-2 and BAX, in the anterior pituitary gland of male rats, have not been modified [ 93 ].…”
Section: Balance Among Cell Proliferation and Apoptosis In Prolactmentioning
confidence: 99%
“…The in vitro and in vivo expression of aromatase is in the lactotroph cell of male rats and is involved in the control of proliferation and prolactin release by transforming testosterone to estradiol [ 41 ]. Moreover, the pituitary aromatase activity could be involved in the regulation of the apoptosis of pituitary cells [ 93 ]. Other studies have shown that, in patients with acromegaly and prolactinoma, aromatase was high, was negatively correlated with Ki-67 score, and was higher in the pituitary of patients with complete postoperative remission than without remission [ 12 ].…”
Section: Balance Among Cell Proliferation and Apoptosis In Prolactmentioning
confidence: 99%
“…The up‐regulation of the Bax/Bcl‐2 ratio and Caspase‐3 expression indicates apoptosis (Simões et al, 2013). DHT plays an anti‐apoptotic role by modulating the AR pathway in anterior pituitary and Sertoli cells of rats (Magri et al, 2016; Simões et al, 2013), granulosa cells of sheep antral follicles (Duan et al, 2021) and U18666A‐induced C6 cells (Bing et al, 2015; Yao et al, 2016). Therefore, we treated sheep epididymal epithelial cells with DHT in vitro and detected the expression of apoptosis‐related factors.…”
Section: Discussionmentioning
confidence: 99%